The influence of using picture story books on the mastery of English vocabulary in early childhood - Sirjon, Sirjon; Setyaningsih, Diana; Sulle, Naomi Mersi (Universitas Islam Sultan Agung, 2025)
The low mastery of English language comprehension in early childhood is a problem that has an impact on the development of children's language skills later. One of the contributing factors is the minimal use of interesting learning media that is in accordance with children's characteristics. This study aims to analyze the impact of the use of picture story books on the mastery of English vocabulary in early childhood. This study used a quasi-experimental method with a one-group pretest-posttest design. The research sample consisted of 15 children aged 5-6 years. The sample was selected by purposive sampling based on the consideration that children aged 5-6 years are likely to be actively involved in English vocabulary learning activities. Data were collected through a comprehension mastery test in the form of word recognition and pronunciation based on pictures. The data analysis technique used a paired t-test. The results showed a significant increase in the average score from 2.07 in the pretest to 3.67 in the posttest, with a significance value of 0.000 (p <0.05). The conclusion of this study is that picture story books have a positive effect on improving early childhood English comprehension. These findings imply the importance of using picture story books as a fun, interactive, and contextual learning medium in language learning in early childhood education. Future scholars are encouraged to build on these findings by further exploring culturally contextualized story content, integrating family involvement, and longitudinal studies examining the long-term impact of storybook-based learning.